Odpowiedzialność za usterki utworu w świetle art. 55 ustawy o prawie autorskim i prawach pokrewnych - Nawłatyna, Karolina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article is an analysis of the legal regulation of liability for defects of a work on the grounds of the currently effective Act on Copyrights and Related Rights. The most important from the substantive point of view aspects of the subject matter are presented, i.e. the subject matter and scope of Article 55 of Act on Copyright and Related Rights, the concept of defects in copyright, the premises for liability for defects in the work and the content of the rights of the ordering party in case of delivery of the work burdened with defects. Due to the fact that Article 55 of the copyright does not constitute the only and full regulation of the rules of liability for defects of the subject matter of the contract, it should have been compared with other solutions adopted in the Polish legal system concerning defects of the subject matter or the law. The point of reference for the analysis undertaken in the article are the provisions on warranty in the sales contract and specific work contract, contained in the Civil Code (respectively: Article 556 et seq and Article 638 of the Civil Code).
Keywords: copyright law; contract on the transfer of autors’s economic rights; ordered work; defects; defects of the work; liability for defective work